IgM and its receptors and binding proteins - Kubagawa, Hiromi; Burrows, Peter D. (Springer, 2017)
This volume reviews the current state of research on the IgM antibody and its multiple receptors and binding proteins. Interactions of the IgM ligands with these molecules are important for protection against infections as a first line of defense, as well as for regulation of immune responses to pathogens and self-antigens. The book includes up-to-date information on: (i) the phylogeny of three IgM-binding receptors [polymeric Ig receptor (pIgR), Fc receptor for both IgA and IgM (Fc?/æR), and Fc receptor for IgM only (FcæR)]; (ii) the lymphocyte-restricted distribution and unique ligand-binding activity of FcæR; (iii) the definition and potential function of Fc receptor-like molecule A (FCRLA) as a resident endoplasmic reticulum protein that binds IgM, but also IgG and IgA; (iv) IgM antibody-mediated enhancement of humoral immune responses, highlighting the importance of complement and its receptors, (v) the numerous important roles of IgM natural antibodies in regulation of inflammation. It is an invaluable resource for researchers and clinicians alike.
Keywords: Immunoglobulin M.; elektronické knihy; electronic books